2010
DOI: 10.1007/s10886-010-9861-8
|View full text |Cite
|
Sign up to set email alerts
|

Formate Analogs as Antagonists of the Sex Pheromone of the Honeydew Moth, Cryptoblabes gnidiella: Electrophysiological, Behavioral and Field Evidence

Abstract: Cryptoblabes gnidiella Milliére (Lepidoptera: Pyralidae) is an economically important exotic pest of vineyards in Southern Brazil and Uruguay. The sex pheromone of C. gnidiella was identified as a mixture of (Z)-11-hexadecenal and (Z)-13-octadecenal, and has been used to monitor populations of this pest in Israel. The development of mating disruption for this species may be hampered by the chemical instability of the natural pheromone components. Therefore, studies on more stable pheromone analogs may provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Besides the antagonist effect probed in vitro , the evidence at behavioral level supports the idea that structural analogs of pheromones can function as antagonists. For example, Sellanes et al ( 2010 ) reported the inhibition of sexual response in the honeydew moth Cryptoblabes gnidiella when the structural analogs, ( Z )-9-tetradecenyl formate and ( Z )-11-hexadecenyl formate, were added to synthetic sex pheromone, ( Z )-11-hexadecenal and ( Z )-13-octadecenal, in wind tunnel tests. This pheromone antagonist effect was later corroborated in field assays, where the trapping of C. gnidiella males decreased in a dose-dependent pattern.…”
Section: Insect Odorant Receptors As Promising Pest Control Targetsmentioning
confidence: 99%
“…Besides the antagonist effect probed in vitro , the evidence at behavioral level supports the idea that structural analogs of pheromones can function as antagonists. For example, Sellanes et al ( 2010 ) reported the inhibition of sexual response in the honeydew moth Cryptoblabes gnidiella when the structural analogs, ( Z )-9-tetradecenyl formate and ( Z )-11-hexadecenyl formate, were added to synthetic sex pheromone, ( Z )-11-hexadecenal and ( Z )-13-octadecenal, in wind tunnel tests. This pheromone antagonist effect was later corroborated in field assays, where the trapping of C. gnidiella males decreased in a dose-dependent pattern.…”
Section: Insect Odorant Receptors As Promising Pest Control Targetsmentioning
confidence: 99%
“…The (Z) isomer is here obtained with high stereoselectivity, with a (Z)/(E) ratio of 9/1. The final stage of the synthetic sequence is the oxidation of (Z)-11-hexadecenol to the pheromone component (Z)-11-hexadecenal (Sellanes et al, 2010) using pyridinium chlorochromate as oxidizing agent in 70 % yield. Acetylation of (Z)-11-hexadecenol with acetic anhydride in the presence of triethylamine and 4-dimethylaminopyridine afforded (Z)-11-hexadecenyl acetate in excellent yield (90 %) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Assim, Sellanes et al (2010) estudaram as respostas eletrofisiológicas e comportamentais de machos de C. gnidiella às formas análogas de (Z)-11-hexadecenal e (Z)-13-octadecenal, dada a importância destes análogos estruturais mais estáveis, para aumentar a eficácia da técnica e potencializar seu uso no manejo de pragas.…”
Section: Resultsunclassified